Stress exposure in nurses and technicians at Clinical Center Foča - Jelena Pavlović; Bojan Joksimović; Vedrana R. Vidojević (Биомедицинска истраживања, 2013)
Introduction: . Nursing is by nature a profession that involves a high level of stress. Stress or stressful reaction is response to stressful situations. Health care workers are exposed to combustion and it is professional nature of their work, especially in clinical hospital practice. The aim of this study was to identify and analyze the stress factors and the level of stress in the workplace of nurses and technicians. Methods: . Research was conducted in the service of internal medicine and neurological wards at Clinical Center Foča. A sample consisted of nurses and technicians employed in these services interviewed in the period from February to March 2012 by means of an anonymous survey. Results: . All surveyed nurses and technicians have a secondary education. Most respondents were female, 100% in the internal ward and 80% in the neurological ward. 75% of health of a total number of surveyed nurses and technicians in the department of internal medicine, 80% of them believe that they are exposed to stress whereas 20% of them deny it. All health care workers in the internal ward and 95% in the neurological ward consider that the relationships in these services are satisfactory. Most health care workers in the internal ward (75%) and more than half of health workers in the neurological ward (55%) believe that the primary stressor of health care workers are the professional requirements. All surveyed health care workers are able to take regular holidays (100%). Most health care workers (70%) are exposed to the risk and hazards in both services. Conclusion: . Our results suggest that exposure to stress in health care workers is present in high percent - age. All health workers are able to take their vacations regularly while a major source of stress is work and professional requirements overload.
Keywords: stress; nurses; professional job; burn-out